Packaging InnoPackaging Innovation as an Effort to Increase the Selling Value of Bu Gan's Frozen Food MSME Productsvation as an Effort to Increase the Selling Value of Bu Gan's Frozen Food MSME Products - Santi, Fitriana; Dalulia, Primahasmi; Trisna June, Cindy Getah; Agesia, Sheina Vella; Fatin, Yustinus Ricky (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was conducted at UMKM Bu Gan, located in Mergan Village, Malang City, with the objective of improving the quality and competitiveness of its frozen food products through the provision of a vacuum sealer machine. The partner’s main challenge was limited packaging capabilities, as the products were previously wrapped using simple plastic packaging, resulting in low durability and anunattractive product appearance. To address this issue, the service team provided training on the importance of hygienic, informative, and appealing packaging, along with hands-on demonstration of  the vacuum sealer machine’s operation. The results indicate that UMKM Bu Gan is now able to operate the machine independently, producing neater and more professional packaging with extended shelf life. The application of this simple technology is expected to strengthen consumer trust, expand marketing opportunities both offline and online, and increase the overall selling value of frozen food products.